CCAFS & GRA CLIFF-GRADS Webinar Series (Session 2): Direct measurement approaches to investigating mitigation options in livestock systems - CGIAR Research Program on Climate Change, Agriculture and Food Security; Global Research Alliance on Agricultural Greenhouse Gases (2019)
Agenda Introduction - Meryl Richards What is the effect of inhibiting methane production in the rumen on nitrogen use efficiency? - Florencia Garcia Evaluation of GHG in pastures with foliar N fertilizers - María De Bernardi Can pasture type influence nitrous oxide emissions from cattle manure? - Banira Lombardi Discussion of presentations Tips for writing and publishing journal articles - Meryl Richards Discussion on writing and publishing Conclusion - Meryl Richards